Typologies: What types of foreign executives are appointed by local organisations and what types of organisations appoint them? - Frithjof Arp (Zeitschrift für Personalforschung (ZfP), 2013)
Current issues in international human resource management include global careers that differ from traditional expatriate assignments. A number of foreign executives have in recent years been appointed to positions in the headquarter operations of culturally distant organisations. These appointments of foreign executives in local organisations (FELOs) can be viewed as a specific form of self-initiated expatriation (SIE), with several distinct types of FELOs found in fieldwork studies. This article offers typologies of the individuals and organisations involved in the FELO phenomenon. These typologies elucidate that FELO appointments do not necessarily indicate a geocentric hiring approach, and assist in identifying which FELO workplaces produce successful outcomes as well as those which are likely to fail. The applicability to other country contexts, implications for theory on diversity in management teams, and key criteria for FELO hiring practices are discussed. – – Zu aktuellen Themen der internationalen Personalforschung zählen globale Karrieren, die sich deutlich von traditionellen Auslandsentsendungen unterscheiden. In den letzten Jahren ist eine Anzahl ausländischer Führungskräfte in die Unternehmenszentralen kulturell ferner Organisationen verpflichtet worden. Diese foreign executives in local organisations (FELOs) können als spezifische Form selbstinitiierter Expatriierung (SIE) betrachtet werden, wobei in Feldstudien dezidiert unterschiedliche Typen von FELOs gefunden wurden. Dieser Artikel legt Typologien der im FELO-Phänomen involvierten Personen und Organisationen vor. Sie zeigen auf, dass die Verpflichtung ausländischer Führungskräfte nicht unbedingt auf geozentrische Personalpraktiken hinweist und helfen, erfolgreiche sowie zum Scheitern neigende Arbeitsverhältnisse zu identifizieren. Die Anwendbarkeit auf unterschiedliche Länderkontexte, Implikationen für Theorien über kulturelle Vielfalt in Managementteams und die wichtigsten Kriterien der FELO Einstellungspraxis werden erörtert. Thema: Führungskräfteauswahl; Executive Recruitment; Ausländische Arbeitskräfte, Interkulturelles Management, Cross-cultural Management; Typologien
Keywords: M12; M14; M16; M51; Z10; 650; foreign executives; expatriates; self-initiated expatriation; cultural distance; typologies; Führungskräfteauswahl; Ausländische Arbeitskräfte; Interkulturelles Management; Typologie